Urethral musculature and innervation in the female rat. Issue 3 (18th January 2015) - Zhang, Xiaoyu; Alwaal, Amjad; Lin, Guiting; Li, Huixi; Zaid, Uwais B.; Wang, Guifang; Wang, Lin; Banie, Lia; Ning, Hongxiu; Lin, Ching‐Shwun; Guo, Yinglu; Zhou, Liqun; et al.
Abstract : Aims: The urethral sphincter and urethral muscle innervation are critically involved in maintaining continence, especially in the female. However, the urethral muscle type and distribution, as well as the urethral nerves are far from being well documented. Our aim was to clearly identify the distribution of urethral striated muscle, smooth muscle, and urethral nerves. Methods: In a cohort analysis of 3‐month‐old female Sprague‐Dawley rats, cross and longitudinal sections of female rat urethra were extensively investigated using morphological techniques. Urethras were harvested to the sections, in order to provide both global and detailed visions of the urethra. H&E, Masson's Trichrome, phalloidin and immunoflourence stains were used. The cytoarchitecture, nitrergic, and cholinergic innervations were mainly investigated. Different layers of the segments of urethra were traced to draw curve graphs that represent the thickness of each muscle layer of urethral wall. Results: The results showed that the primary peak of striated muscle is in the middle urethra. The inner layer close to mucosa was found to contain longitudinal smooth muscle. Near the bladder orifice, the circular smooth muscle dominates, which becomes thinner distally throughout the rest of urethra. In the middle urethra the vast majority of the urethral muscle are circularly oriented striated muscle cells. Typical nerve endings were present in high power images to show the different characteristic features of nerve innervation. Conclusions: This study has illustrated the detailed morphological structure and innervations of the normal female rat urethra and can serve as a basis for further study of stress urinary incontinence (SUI). Neurourol. Urodynam. 35:382–389, 2016 . © 2015 Wiley Periodicals, Inc.